Macropropagation of Teak (Tectona grandis L.F.) - Nautiyal, S.; Rawat, M. S. (Indian Forester, 1994)
With growing trends towards more and more plantation forestry and genetic improvement of economic forest trees, it has become necessary to develop quick and economic methods of producing planting material. In teak macropropagation by cleft grafting, budding and branch cutting has been successfully employed for establishing clones of desired quality. Almost 80 to 100 per cent success was obtained in case of cleft grafting and bud grafting however, maximum 60 per cent success was recorded by rooting of branch cuttings. The other methods of propagation like air layering etc. were not successful in this species.